Characterization of microstructure and mechanical properties of continuous and pulsed current gas tungsten arc welded superaustenitic stainless steel. Issue 10 (4th May 2015) - Devendranath Ramkumar, K.; Choudhary, Ayush; Aggarwal, Shivang; Srivastava, Anubhav; Harsha Mohan, Tadikonda; Arivazhagan, N.
Abstract: Abstract : The present study investigates the joining of 5-mm-thick plates of superaustenitic stainless steel, AISI 904L by continuous current (CC) and pulsed current (PC) gas tungsten arc welding (GTAW) using ER2553 and ERNiCrMo-4 fillers. This research article attempts to provide a detailed structure–property relationship of these weldments. Interface microstructure revealed the absence of deleterious secondary phases at the heat affected zone in all the cases. Skeletal delta ferrite morphology at the cap of ER2553 fusion zone and multidirectional grain growth at the ERNiCrMo-4 fusion zone were observed for both the weldments. The average hardness at the fusion zone was found to be higher for PCGTA weldments using ER2553 due to the higher proportions of ferrite. Tensile studies corroborated that the failure occurred at the parent metal in all the cases. Charpy V-notch studies divulged that the CCGTA and PCGTA weldments utilizing ERNiCrMo-4 filler exhibited the greater impact toughness of 69 J and 75 J, respectively. The bend test results conveyed that both the CCGTA and PCGTA weldments using ERNiCrMo-4 exhibited soundness and ductility.